Issues and conceptual framework for museum spatial and exhibition design in China - Sijia, Zhang; Hazim, Zulkarnain; Abdul Karim, Norashikin (UiTM Press, 2025)
This study reviews theories on the impact of spatial design and display systems on audiences in Chinese museums and unpacks how spaces and display systems affect audiences. With the rapid development of Chinese museum industry, diversified exhibition design is a prerequisite for museum development. For example, various display systems provide visitors with comprehensive information and improve their visiting experience, resulting in a mutually beneficial relationship between visitors and museums. At the same time, museums are constantly refining their spatial design to enhance visitors’ experience and ensure effective use of space. Therefore, it is crucial to understand the impact of spatial and exhibition design factors in museums on the visitor experience. This study provides a comprehensive review of journals, books, conference papers, and other textual resources to establish a framework for understanding how museum space and exhibition design can affect the visitor experience. The purpose of this study is to develop a conceptual framework for museum spaces and exhibitions in China. For instance, to improve visitors’ visiting experience and space utilisation in the museum, Chinese museum designers should optimise functional space and good design of basic configurations. Moreover, the display system can be achieved through dynamic and static displays, ergonomic principles, colour use, and the choice of display cases. This study also aims to contribute to the literature by proposing design concepts to form the basis for future museum layouts and exhibition display system designs. At the end of this study, the author provides valuable insights into design decisions for museums in China.